The impact of failed novel technology and technical errors on the revision burden in total hip arthroplasty: what percentage of revision hip arthroplasty was potentially avoidable?. Issue 6 (November 2022) - Brown, Matthew L; Dunn, Justin M; Early, Samuel; Challa, Sravya; Ezzet, Kace A
Background: Despite the high success rate of total hip arthroplasty (THA), new implant technologies continue to be developed. Although potentially useful, such novel developments may result in unintended consequences, leading to revision surgery, often prematurely. In several instances, new technology that appeared promising was later found to be inferior to existing technology and resulting in early revision surgery. Additionally, technical surgical errors may also lead to early revisions. Some have argued that revisions related to such phenomena are potentially avoidable. The present analysis investigates to what extent the contribution of "failed new technology" and "technical errors" contributes to the revision burden and to the need for premature revision arthroplasty. Methods: We retrospectively analysed 432 revision THAs and categorised them as either "late revisions" based on survivorship of 10 years or "premature revisions". Among both cohorts, we determined what percentage of revisions were potentially avoidable and due to failed novel technologies and technical errors, and what percent were "unavoidable". Results: Of the 432 revisions, 267 (62%) were considered premature and 38% were considered late. Of the premature revisions, 108 were considered potentially avoidable (81 failed novel technologies, 27 technical errors). Conclusions: Our data demonstrates that new technology and surgical techniques can result in premature failure of THA. Surgeons should take caution when incorporating new implant technology or surgical techniques into their practice.